RELATIONSHIP BETWEEN TEACHER AFFECTION AND STUDENTS’ EMOTIONAL ADJUSTMENT IN PUBLIC BOARDING SECONDARY SCHOOLS IN NAIROBI COUNTY, KENYA. - Josephine, Keino Kangogo; Ngari, Stephen Mbugua; Kimani, James Mwaura (IJRDO- Journal of Educational Research, 2022)
Globally, student maladjustment in schools has been associated with different factors. This is not different from Kenyan schools and specifically schools in Nairobi County. This problem of adjustment is one of the vital issues of student life in boarding secondary school especially in today’s complex society; therefore, it is a matter of serious consideration despite guidance and counselling programs in schools. The purpose of this study was to examine the relationship between teacher affection and students’ emotional adjustment in public boarding secondary schools in Nairobi City County, Kenya. The study adopted Ex post facto research design. To gather data, a developed questionnaire was administered to secondary school students in Form one and two who at this time are in the process of adjusting to school. To get a general understanding of student school adjustment, 24 class teachers were interviewed. The study was guided by Bronfenbrenner’s Bio ecological systems theory, Ceci, and Connell’s Self-Determination theories. The target population was 7,123 students. Stratified random sampling was used to obtain a sample of 692, among them were 335 boys and 357 girls. To ensure validity, the researcher sought the expert opinion of her supervisors who checked the face and content validity against the stated objectives. Reliability of instruments was established by use of Cronbach Alpha and a reliability coefficient of 0.7 or higher was considered acceptable. Student questionnaire was administered by the researcher with the help of class teachers of the six sampled schools. The interview schedule was administered personally by the researcher. The collected data was then organized and summarized by use of descriptive statistics and analyzed by use of statistical package for social sciences (SPSS) computer programme version 21.0 and presented in percentages, means, in tables and figures. Pearson Product Moment Correlation coefficient was used to determine the relationship between variables and a significance level of 0.05 was used to test the null hypothesis. Data from interviews was analyzed based on emerging themes and reported in a narrative form. The study found that adjustment to boarding school is a challenge to form one and form two students. The findings may be used to improve student adjustment in public boarding secondary schools. It may also form a base for further research on affective teacher-student relationship.